Survey of ICT and Education in Africa : Mali Country Report - Fall, Babacar (World Bank, Washington, DC, 2012)
This short country report, a result of larger Information for Development Program (infoDev) - supported survey of the Information and Communication Technologies (ICT) in education in Africa, provides a general overview of current activities and issues related to ICT use in education in the country. Mali has a national policy and strategic plan for ICT, administered through the Information and Communications Technology Agency (AGETIC). One of its missions is to set up an empowering environment for the promotion and use of ICT in education and capacity building for the formal and non-formal sectors. Though certain challenges obstacles persist - such as a very low level of development of the telephone networks and no direct access to an Internet backbone - a number of actors, including the Ministry of Education, local and international public and private partnerships, and many others, remain committed to enhancing Mali's education system. Notable Initiatives in the formal system include a university intranet, the Nepad e-Schools Demo project, internet in schools, SchoolNet Mali and, in non formal education, the United Nations Educational, Scientific, and Cultural Organization (UNESCO) Community Multimedia Centre Scale-Up Project which enables ICT access for villages.